2008
DOI: 10.1017/s0265021507003043
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine stress response and inflammatory activation during CABG surgery. A randomized trial comparing remifentanil infusion to intermittent fentanyl

Abstract: The perioperative endocrine stress response was attenuated in patients supplemented with continuous remifentanil infusion as compared to intermittent fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 28 publications
4
48
0
5
Order By: Relevance
“…decreased in cardiac patients using remifentanil (7). When comparing the cardiac protective effect of remifentanil with fentanyl, lower CKMB and troponin T levels were observed with remifentanil (24,25). In this study, CKMB levels and lactate levels at T2 were lower in the sevoflurane-dexmedetomidine group than in the sevoflurane-remifentanil group at all times.…”
Section: Discussionmentioning
confidence: 43%
“…decreased in cardiac patients using remifentanil (7). When comparing the cardiac protective effect of remifentanil with fentanyl, lower CKMB and troponin T levels were observed with remifentanil (24,25). In this study, CKMB levels and lactate levels at T2 were lower in the sevoflurane-dexmedetomidine group than in the sevoflurane-remifentanil group at all times.…”
Section: Discussionmentioning
confidence: 43%
“…In this study, both remifentanil and fentanyl attenuated the elevation of troponin T and CK-MB after cardiac surgery and the levels of postoperative cardiac enzymes in the remifentanil group were kept significantly lower compared with the fentanyl group. Similarly, Winterhalter et al [29] reported there was a trend towards lower CK-MB level in the remifentanil group and statistically lower CK-MB and a trend towards lower troponin T level.…”
Section: Discussionmentioning
confidence: 77%
“…23,24 This may be the reason why no difference between groups was observed. A follow-up study might include cardiac patients with similar renal dysfunctions to compare ketamine and remifentanil in terms of their immune protective effects determined by more elaborated markers.…”
Section: Discussionmentioning
confidence: 94%